1998
DOI: 10.1161/01.atv.18.2.250
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Activation of Prothrombin on the Vascular Wall After Arterial Injury

Abstract: Abstract-This study was designed to characterize the relative roles of bound Xa/Va and thrombin activity in vascular wall procoagulant activity after balloon-induced injury and the extent to which intravenous aspirin and heparin attenuate procoagulant activity associated with the vascular wall. Abdominal aortic injury was induced in rabbits by overinflation and multiple passages of a 4F embolectomy catheter. Rabbits were killed 15 minutes or 4,8,24,48, 72, 96, or 120 hours after injury. Aortic segments were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 63 publications
(63 reference statements)
2
29
0
Order By: Relevance
“…20 Measurements of thrombin activity bound to the wall of balloon-injured rabbit arteries reveals that local thrombin generation peaks within the first 24 to 48 hours after acute injury but may persist at low levels for more than 7 days. 16,17,21 Similar measurements in vein grafts have not previously been reported. In the present study, the extent of local thrombin generation in vein grafts was found to be of the same magnitude as in injured arteries but with a later peak and of longer duration.…”
Section: Local Thrombin Generation In Vein Graftssupporting
confidence: 83%
See 2 more Smart Citations
“…20 Measurements of thrombin activity bound to the wall of balloon-injured rabbit arteries reveals that local thrombin generation peaks within the first 24 to 48 hours after acute injury but may persist at low levels for more than 7 days. 16,17,21 Similar measurements in vein grafts have not previously been reported. In the present study, the extent of local thrombin generation in vein grafts was found to be of the same magnitude as in injured arteries but with a later peak and of longer duration.…”
Section: Local Thrombin Generation In Vein Graftssupporting
confidence: 83%
“…16,17 Freshly excised vessels were washed with HBSS and placed in the template as described above. Because of the technical inability of placing rabbit jugular vein segments into the template reliably without exposing their adventitial surface to the substrate, rabbit inferior vena cavae (IVC) were used as venous controls.…”
Section: In Situ Protein C and Thrombin Activity Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…17 The procoagulant status of the vessel wall due to vascular injury or atherosclerosis leads to adhesion and accumulation of platelets, initiation of coagulation cascades, and enhanced thrombin generation. 18 Therefore, modulation of thrombogenesis and fibrinolysis has been a major focus in atherosclerosis research.…”
Section: Discussionmentioning
confidence: 99%
“…This rupture initiates hemostasis in the blood vessel and leads to activation of thrombin and a thrombus to form at the site of rupture. Elevated levels of activated thrombin bound to the vessel wall have been observed up to 72 h after vascular injury (3). These elevated thrombin levels not only induce clot formation but also have been implicated in the progression of atherosclerosis by causing smooth muscle cells to bind circulating low density lipoprotein (4).…”
Section: Ardiovascular Disease Affects 1 In 3 People In the Unitedmentioning
confidence: 99%